2008
DOI: 10.1166/jnn.2008.d260
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Characteristics and Superelasticity of Ti-Ni-Cu Alloy Ribbons with Nano Ti2Ni Particles

Abstract: Microstructures and deformation behaviour of Ti-45Ni-5Cu and Ti-46Ni-5Cu alloy ribbons prepared by melt spinning were investigated by transmission electron microscopy, thermal cycling tests under constant load and tensile tests. Spherical Ti2Ni particles coherent with the B2 parent phase were observed in the alloy ribbons when the melt spinning temperature was higher than 1773 K. Average size of Ti2Ni particles in the ribbons obtained at 1873 K was 8 nm, which was smaller than that (10 nm) in the ribbons obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…After 10 h mechanical milling, the orthorhombic phase is the majority one and by increasing the milling time, the content of monoclinic and non-transforming Ti 2 (NiCu) phases increases. This last phase was generally reported in Ti rich NiTi based alloys prepared by classical routes but also in thin films or melt spun ribbons, being always induced after a thermal treatment [10,11]. For under discussion samples, the Ti 2 Ni phase is most probably formed by a eutectic reaction at 942C during the sintering process (at 950C).…”
Section: Tablementioning
confidence: 69%
“…After 10 h mechanical milling, the orthorhombic phase is the majority one and by increasing the milling time, the content of monoclinic and non-transforming Ti 2 (NiCu) phases increases. This last phase was generally reported in Ti rich NiTi based alloys prepared by classical routes but also in thin films or melt spun ribbons, being always induced after a thermal treatment [10,11]. For under discussion samples, the Ti 2 Ni phase is most probably formed by a eutectic reaction at 942C during the sintering process (at 950C).…”
Section: Tablementioning
confidence: 69%
“…[1][2][3][4] Therefore, various high-k materials have been proposed for the advanced nanoscaled Flash memory application. [1][2][3][4][5][6] For example, it has been reported that the P/E speeds of Flash memory with a Hf-or Al-based charge trapping layer were enhanced for the enlarged c or enlarged v 2 3 Among the high-k trapping materials, it is noted that the dual phase TiO x N y /TiN could be a promising candidate for the Flash memory application due to the midgap work function (4.6 eV) 7 of TiN which makes a deeper quantum well ( c compared to the electron affinity of Si or Ge. On the other hand, TiO x has deep v (3.4 eV) to SiO 2 .…”
Section: Introductionmentioning
confidence: 99%